INTERNATIONAL DISSEMINATION OF “BOOK SCIENCE” PUBLICATIONS: BIBLIOMETRIC ANALYSIS - MIKNIENĖ, GIEDRĖ (Knygotyra, 2013)
This paper introduces a quantitative study of research in book science, throwing light on one aspect of scientific communication – the worldwide dissemination of scientific news published in the serial “Book Science” („Knygotyra“). The latter has been selected as the research object because it is the only specialized Lithuanian publication on the topic, containing the majority of papers in book science and related fields, published in the state. In Lithuania, “Book Science” is recognized as a publication meeting the today’s scientific requirements and ensuring a high quality of its articles. The study period is 2000–2011. The research has employed qualitative methods, such as analysis of the qualitative characteristics of the publication flow and citations. The analysis of the scientific production of “Book Science” has been carried out in eight aspects crucial for the effective worldwide dissemination of scientific data: publication language, the language and length of summaries, internationality, international co-authorship, the international composition of the editorial board, open access to electronic publication, references in international databases, international citing. The research has revealed “Book Science” to have a strong potential for being noticed and read by international readers because: 1. papers in languages other than Lithuanian make up 27.4 per cent of the total number of its articles; 2. articles in Lithuanian have summaries in another language (most often in English); 3. the proportion of publications by foreign authors in the journal is 26.6 percent; such authors represent 16 countries; 4. the international editorial board includes specialists from six countries (Estonia, Germany, Poland, Latvia, Russia, and Finland); 5. the digital version of “Book Science” is openly accessible online; 6. “Book Science” is referenced in five international and three Lithuanian databases; information about the journal with the links to its online site is given in four electronic resources; 7. citation data for “Book Science” are given by the Google Scholar international search engine and in the Lithuanian database “Lithuanistics”; 8. the journal is distributed in 20 countries worldwide. “Book Science” does not conform to only two criteria of the effective worldwide dissemination of publications: 1) there is not a single case of international co-authorship; 2) the international citation level of the journal’s articles is low. International co-authorship and international citing are more usual in the case of physical, biomedical, and technological sciences. Due to the specifics of humanities and social sciences, their researchers most often work individually, so the number of papers written by more than one author is very small. As to the low international citation level, it is caused by the circumstance that the main aim of this scientific area is to foster the national scientific potential. The present research has confirmed the fact that the majority of articles in the field of book science are oriented to the science of Lithuania. This is indicated by their language, national-oriented topics, translations into Lithuanian of theoretical and methodological articles by foreign authors. The research has demonstrated that “Book Science” meets six out of the eight criteria of effective international dissemination – the fact that shows the book science of Lithuania to integrate successfully into international science, meanwhile retaining its national significance.